UNIVERSALITY OF THE HUMAN SPIRIT : A New Focus for Asian Theological Reflection - Pathrapankal, Joseph (Asian Horizons, 2011)
The Decree on the Missions (Ad Gentes), and the Declaration on World Religions1 (Nostra Aetate) by Vatican II in 1965 were unique events in the history of the Church, both happening towards the end of the Council after very long and crucial discussions and deliberation. These documents are also to be seen as great achievements of Vatican II in relation to the Church’s place in the world in the context of religious pluralism and also the Church’s attitude towards secular history through the openness it gained as a result of the long discussions among the Fathers of the Council. Already in 1964 a brief statement on missions was presented, which concentrated largely on juridical and organizational problems of mission and so it was rejected by the Council. This final Decree is a marked improvement, particularly in theological contents. It is to be clearly stated that the Decree opens up a new approach in the missionary activity of the Church.